2006
DOI: 10.1017/s0266462306050902
|View full text |Cite
|
Sign up to set email alerts
|

Value of magnetic resonance cholangiopancreatography in the diagnosis of biliary abnormalities in postcholecystectomy patients: A probabilistic cost-effectiveness analysis of diagnostic strategies

Abstract: Background: Endoscopic retrograde cholangiopancreatography (ERCP) is considered the gold standard for imaging of the biliary tract but is associated with complications. Less invasive imaging techniques, such as magnetic resonance cholangiopancreatography (MRCP), have a much lower complication rate. The accuracy of MRCP is comparable to that of ERCP, and MRCP may be more effective and cost-effective, particularly in cases for which the suspected prevalence of disease is low and further intervention can be avoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 20 publications
0
11
1
Order By: Relevance
“…Consistent with previous studies this study finds that initial MRCP or EUS to select patients for ERCP are cost-effective compared with direct ERCP. [ 23 26 ] Unlike other studies results in this study are not sensitive to varying the probability that CBD stones were present. [ 23 , 26 ]…”
Section: Discussioncontrasting
confidence: 54%
See 3 more Smart Citations
“…Consistent with previous studies this study finds that initial MRCP or EUS to select patients for ERCP are cost-effective compared with direct ERCP. [ 23 26 ] Unlike other studies results in this study are not sensitive to varying the probability that CBD stones were present. [ 23 , 26 ]…”
Section: Discussioncontrasting
confidence: 54%
“…[ 23 26 ] Unlike other studies results in this study are not sensitive to varying the probability that CBD stones were present. [ 23 , 26 ]…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…The primary outcome measure was the QALY, which is a composite measure of the length and quality of life; 1 QALY is defined as 1 year lived in perfect health. Following the approach used by Morris and co‐workers to identify the most appropriate utility values, a review of the Cost‐effectiveness Analysis Registry was conducted and 20 studies identified. The utility scores in this analysis were taken from a single study ( Table S3 , supporting information).…”
Section: Methodsmentioning
confidence: 99%